Influence of CaO Content on the Fly Ash–Lime System Hydrothermal Synthesis Reaction Under Autoclave Curing - Zhu, Chenhui; Lou, Yilong; Shen, Xuemei; Xu, Hesi; Yang, Jie (Frontiers in Physics, 2021)
As a substitute for traditional Portland cement, the development and research of “low-temperature-synthesized fly ash cement” has been receiving extensive attention. This study explores the effects of calcium oxide content on the fly ash–lime system hydrothermal synthesis reaction under autoclave curing, focusing on the effects of CaO content on the strength of the cement paste. The changes in phase composition, microstructure, and morphology were characterized using X-ray diffraction and scanning electron microscopy (SEM) analysis. The results show that with an increase in the CaO content, the amounts of β-C2S and C12A7 in the gelling material also increase. However, when the CaO content is very high, the amounts of β-C2S and C12A7 in the gelling material no longer increase, and the strength is lost.